A unique case of magnet ingestion with respect to presentation and management - Yalçın, Sule; Karnak, İbrahim and Ekinci, Saniye and Şenocak, Mehmet Emin (The Turkish Journal of Pediatrics, 2012)
Magnet ingestion may lead to serious complications with delay in diagnosis and treatment. The forceful attraction between magnets, with gastric and/or intestinal wall entrapped between them, can cause injury through pressure necrosis. The radiological appearance of more than one magnet on X-ray can be easily misinterpreted as belonging to only one rod-like radiopaque foreign body, even if the magnets are located in different parts of the gastrointestinal tract, thus delaying the management up to the onset of emergent surgical complications. A 17-month-old female with ingestion of a pair of magnets is presented, together with introduction of the clinical picture and therapeutic approach, which differed from the other previously reported cases. The ovoid shape of the magnets, their localization in the gastrointestinal tract (leading to entrapped gastric and intestinal wall between them), absence of any complication, and the therapeutic approach of endoscopic retrieval are the main distinguishing features of this case from those previously reported.